Use of direct oral anticoagulants in the treatment of left ventricular thrombi: A tertiary center experience and review of the literature. Issue 1 (22nd November 2018) - Shokr, Mohamed; Ahmed, Abdelrahman; Abubakar, Hossam; Sayedahmad, Ziad; Rashed, Ahmed; Afonso, Luis; Cardozo, Shaun
Key Clinical Message: Direct oral anticoagulants can potentially provide a more convenient oral alternative for the management of left ventricular thrombi than Warfarin. These medications do not require frequent monitoring and have less drug‐drug interactions. Randomized controlled trials are needed to further demonstrate their efficacy and safety in this setting. Abstract : Direct oral anticoagulants can potentially provide a more convenient oral alternative for the management of left ventricular thrombi than Warfarin. These medications do not require frequent monitoring and have less drug‐drug interactions. Randomized controlled trials are needed to further demonstrate their efficacy and safety in this setting.